Hallazgo de banchopsis caudatus kasparyan & ruíz (hymenoptera: ichneumonidae: banchinae) en el estado de Hidalgo, México - Ruíz-Cancino, Enrique; Khalaim, Andrey I.; Coronado-Blanco, Juana Ma. (Instituto de Ecología, A.C., 2010)
Banchopsis caudatus is registered from the State of Hidalgo, Mexico. This is the second record of this species at world level